Pigmentation of axillary sentinel nodes from extensive skin tattoo mimics metastatic melanoma: case report. (30th December 2013) - Manganoni, Ausilia Maria; Sereni, Elena; Pata, Giacomo; Ungari, Marco; Pavoni, Laura; Farisoglio, Camillo; Calzavara‐Pinton, Pier Giacomo; Farfaglia, Roberto
Abstract Background The relationship between the occurrence of skin diseases and skin tattoos remains unclear. Dermatologic disorders have been reported to occur in about 2% of cases. In addition, tattoo pigment can migrate to the regional lymph nodes through the lymphatic vessels and subsequently mimic metastatic disease from melanoma. Methods A 23‐year‐old Caucasian man presented with a pigmented lesion on the left scapular region, which had slowly enlarged over time. The patient exhibited an extensive tattoo on the left upper arm, left shoulder, and part of the upper back. His medical history was unremarkable. The pigmented lesion was excised. Histology confirmed malignant melanoma. Ultrasound examination of the abdomen, neck, and inguinal and axillary lymph nodes and a total body computed tomography scan showed no sign of disease. A re‐excision with 2‐cm margins and sentinel lymph node biopsy (SLNB) were performed. Two grossly enlarged, black sentinel lymph nodes (SLNs) highly suggestive of melanoma metastases were removed. Results No evidence of melanoma metastasis was found in any of the sampled tissues. Large amounts of pigment were present within the subcapsular space and sinusoid areas of the two clinically suspicious lymph nodes. Immunohistochemical analysis was negative. Conclusions Sentinel lymph node biopsy is widely performed in cutaneous melanoma. Histologic confirmation of any enlarged, pigmented SLN is essential prior to radical surgery, especially when pigmented SLNs are found near a tattoo. Tattoo pigments may deposit in the regional lymph nodes and may clinically mimic metastatic disease. A history of tattooing should be considered in all melanoma patients eligible for SLNB. In a finding of darkly pigmented nodes during SLNB, radical lymphadenectomy should be withheld until immunohistologic confirmation of metastasis in the SLN is obtained.